Implementation of The Project-Based Learning Model (PjBL) to Improve Students' Biological Learning Results at MAN Insan Cendekia Palu City - Amalia, Rezki; Latief, Riskayati (Biology Teaching and Learning, 2023)
AbstractThe purpose of this study was to improve students' biology learning achievement in Animalia material by using the Project Based Learning (PjBL) model. The research subjects were students of class X IPA Al-Qomar MAN Insan Cendekia Kota Palu even semester of the 2022/2023 academic year that consist of 24 students. This research uses collaborative classroom action research (PTKK). The research was carried out in two cycles, each cycle was carried out in 2 meetings through four stages, namely planning, actions, observing and reflecting. The results showed that the application of the Project based learning (PjBL) model could improve students' biology learning achievement with an average score in cycle I of 77.85 and in cycle II learning achievement increased with an average score of 87.10. Posttest results showed an increase in student learning achievement in the form of classical comprehend of 96% and an increase in absorption of 46.85%.Key words: Project based learning, learning achievement, Animalia